Analysing the Case of Rohingya Refugees In Bangladesh: Different Levels of Solidarity - Salsabeel, Nahian; Leera, Faria Ulfath (PARTECIPAZIONE E CONFLITTO, 2023)
The Rohingya refugee crisis has been a prolonged refugee crisis in Bangladesh. With the first refugee influx having taken place as far back in late 1977, to the latest one in 2017 (MSF, 2022), the protracted nature of the crisis has made the refugees extremely volatile. The Bangladeshi people warmly welcomed the Rohingya refugees in the face of the 2017 Myanmar military crackdown against the minority, citing four main reasons for the feelings of solidarity – (i) religious similarities, (ii) historical cultural and linguistic linkages, (iii) solidarity from political parties, and (iv) the historical experience of Bangladesh during the liberation war. To add to this, one can also cite constitutional and international duties as humanitarian motivation for Bangladesh to host the refugees. This research will focus on indications of solidarity expressed by actors from state actors and non-state actors through their policies and actions at individual, state and international levels. It will view the issue of expression of solidarity with Rohingya refugees in Bangladesh with the multi-focal lens of levels of analyses. In doing so, the study poses the questions: How is solidarity expressed at the individual, state, and international levels in the context of the Rohingya refugee crisis in Bangladesh? Throughout the study, we link how certain policies, actions and narratives are indicative of expressions of solidarity with the Rohingya refugee population in Bangladesh, especially after the August 2017 Rohingya refugee influx. In doing so the illustrates expressions of solidarity towards the Rohingya refugees at different levels, and also explained some of the justifications of such solidarity. Much of the motivations for the expressions of solidarity has come from sentiments of empathy, global community, neighborly affection and respect and sense of duty from religious, cultural, historical, international human rights and legal obligations.